HAK DESAIN PAKAIAN MENURUT UNDANG-UNDANG NOMOR 31 TAHUN 2000 TENTANG DESAIN INDUSTRI - Haq, Miftahul; Harahap, Irawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to: (1) analyze the form of legal protection for clothing design rights holders under Law Number 31 of 2000 concerning Industrial Design; (2) identify obstacles in the legal protection process; and (3) formulate efforts to overcome these obstacles. This research employs a normative legal method, with secondary data sources consisting of literature related to intellectual property, industrial design, and statutory regulations. The results indicate that legal protection is provided through preventive measures-by registering industrial designs with novelty elements-and repressive measures-by enforcing laws against infringements, either through litigation or alternative dispute resolution. Major obstacles include low public awareness, limited government socialization efforts, complicated registration bureaucracy, and relatively high registration fees. Improvement efforts involve revising the law, utilizing information technology for online registration, enhancing law enforcement capacity, and strengthening the role of both government and society in protecting industrial design rights.Keywords: Legal Protection, Industrial Design, Exclusive Right.